Target-Based Radiosensitization Strategies: Concepts and Companion Animal Model Outlook - Berry, Matthew R.; Fan, Timothy M. (Frontiers in Oncology, 2021)
External beam radiotherapy is indicated in approximately 50-60% of human cancer patients. The prescribed dose of ionizing radiation that can be delivered to a tumor is determined by the sensitivity of the normal surrounding tissues. Despite dose intensification provided by highly conformal radiotherapy, durable locoregional tumor control remains a clinical barrier for recalcitrant tumor histologies, and contributes to cancer morbidity and mortality. Development of target-based radiosensitization strategies that selectively sensitizes tumor tissue to ionizing radiation is expected to improve radiotherapy efficacy. While exploration of radiosensitization strategies has vastly expanded with technological advances permitting the precise and conformal delivery of radiation, maximal clinical benefit derived from radiotherapy will require complementary discoveries that exploit molecularly-based vulnerabilities of tumor cells, as well as the assessment of investigational radiotherapy strategies in animal models that faithfully recapitulate radiobiologic responses of human cancers. To address these requirements, the purpose of this review is to underscore current and emerging concepts of molecularly targeted radiosensitizing strategies and highlight the utility of companion animal models for improving the predictive value of radiotherapy investigations.